(3OQQ GdeLjO GdaGFV aj HMhQ GdJLhjOs - (3GdeNJGQ Hf MHjH Gddgs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3hHYO aEfi deG aJM Gddg Ydi HYde eSGFd GdJLhjO bd ef JfHg dgG ef Pci hHdjO hcKQ EfcGQ HYVgG QGjJ Cf ffXe HYV ahGFOgG ef Gdege afXeJ ai Pdc fXekG SejJg OQQ GdeLjO GdZGFU ai HMhQ GdJLhjO s
(3BNQgG (B:s
(3hef eMGSf ESeGYjd GdCTQa Cfg deG Gda eLO GdOjf GdbGehSi hQaYg GdCQa hGJab Cf QaY Edi GdMVQI TeS GdOjf Hf GdLRQi ebOeJg GdeYQhaI ai GdJLhjO eY Cf GdebOeI dGJHdZ bOQ hQbI ef GdbGehS QMeg Gddg hCMSf LRGAg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI efXheI heTQhMI s
(3Ydi ghGeTgG HYV GdJUMjMGJ hGdJaSjQ s
(3cJHJ YfGhjfgG HGdMeQI s
(3bQf GdfSN (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs